RISK BEHAVIOR AND FAMILY SATISFACTION IN ADOLESCENTS - Halkovicova, Katarina (IJRDO - Journal of Social Science and Humanities Research, 2018)
The main purpose of present study was to describe the relationship between selected forms of risk behaviors in adolescents (such as alcohol/nicotine abuse, illicit drugs abuse, internet and mobile phone overuse, antisocial behavior, selfharm and suicidal behavior and eating disorders) and family satisfaction. The sample consisted of 62 high school students aged 15- 16 years. To obtain the data, we used the questionnaire detecting risk behavior and Family Satisfaction Scale. The statistically significant relationship between the level of family satisfaction and the incidence of antisocial behavior (p <0.05) and between the occurrence of self-harm and suicidal behavior (p <0.05) was confirmed.